Is there scope for improving balance between RuBP-regeneration and carboxylation capacities in wheat at elevated CO2? - Mitchell, R A (Journal of experimental botany, 2000)
Carboxylation and RuBP-regeneration capacities, which determine light-saturated photosynthetic rate, were analysed in leaves of spring wheat (Triticum aestivum L. cv. Minaret) grown under different atmospheric CO2 partial pressure (pCa) and N supply regimes. Capacities were estimated from a large number of gas exchange, Rubisco and ATP-synthase content measurements, and from these, the pCa at which the two capacities are equal was derived, to allow direct comparison with growth pCa. Acclimation of the balance between the two capacities to growth at elevated pCa in wheat was only partial and appears to occur mostly in older flag leaves and at low N. However, in contrast to conclusions drawn from previous analyses of these data, there was evidence of a specific effect of growth at 70 Pa pCa, where carboxylation capacity is reduced more than RuBP-regeneration capacity for a given leaf N content. A model was used to estimate the effects of fluctuations in PPFD and temperature in the growth environment on the optimal balance between these capacities. This showed that the observed balance between carboxylation and RuBP-regeneration capacities in young wheat leaves could be consistent with adaptation to the current, or even the preindustrial pCa